2011
DOI: 10.1074/jbc.m111.275776
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Proximity of ATP Synthase Subunits 6 (a) in the Inner Mitochondrial Membrane and in the Supramolecular Forms of Saccharomyces cerevisiae ATP Synthase

Abstract: Background:The mitochondrial ATP synthase adopts oligomeric structures. Results: Cross-linking between two subunits 6 (a) indicates their proximity in the ATP synthase dimer. Conclusion: Subunit 6 participates in the ATP synthase monomer-monomer interface. Significance: Learning how the ATP synthases assemble is essential for understanding their involvement in the control of the biogenesis of the inner mitochondrial membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…However, the secondary structure of the N-terminus of subunit a (containing Cys23) suggests that it may be flexible and thus allow convergence within the minimal distance required for disulfide bond formation. This would be consistent with the observation that Cu 2+ -induced a-a dimers form at room temperature but not on ice [45]. In keeping with these findings, a Δe strain carrying a homoplasmic C23S mutation on subunit a no longer formed dimers after treatment with Cu 2+ even at low detergent concentrations (Fig.…”
Section: +supporting
confidence: 90%
See 1 more Smart Citation
“…However, the secondary structure of the N-terminus of subunit a (containing Cys23) suggests that it may be flexible and thus allow convergence within the minimal distance required for disulfide bond formation. This would be consistent with the observation that Cu 2+ -induced a-a dimers form at room temperature but not on ice [45]. In keeping with these findings, a Δe strain carrying a homoplasmic C23S mutation on subunit a no longer formed dimers after treatment with Cu 2+ even at low detergent concentrations (Fig.…”
Section: +supporting
confidence: 90%
“…Cu 2+ has been widely used to investigate thiol-mediated protein-protein interactions and organization of yeast F-ATP synthase. Biochemical studies suggested that homodimers form at subunit a via its unique Cys23 [45]. In the recent F o map, Cys23 residues of adjacent subunits face one another at an estimated distance of 22 Å (Fig.…”
Section: +mentioning
confidence: 95%
“…Consistent with this possibility, we did detect dimers in BN-PAGE after treatment with CuCl 2 (Fig. 4D), which promotes formation of disulfide bridges between adjacent cysteine residues of the monomers (45,47,48). Not all of the monomers dimerized after CuCl 2 treatment (Fig.…”
Section: Purified F-atp Synthase Dimers Possess Channel Activity-supporting
confidence: 78%
“…The fit places CypD close to regions of the peripheral stalk that are likely to contain the N-terminal part of subunit b (Fig. S2 A and B, magenta) (37,38), for which there is at present no X-ray structure. However, more recently, Giorgio et al reported that CypD interacts with the ATP synthase subunit OSCP (39), which is located on top of the F 1 head (Fig.…”
Section: Resultsmentioning
confidence: 93%